Have Racial and Ethnic Disparities in Sentencing Declined? - King, Ryan D. (Crime and justice, 2019)
Blacks and Hispanics convicted of felonies are more likely than whites to receive prison sentences for their crimes, and they receive slightly longer sentences if imprisoned. Yet the majority of prior research compares sentencing decisions at a single point in time and does not give explicit attention to whether and how racial and ethnic disparities have changed. Decades of sentencing data from Minnesota, the federal courts, and a sample of large urban counties are used to assess the degree of change in racial and ethnic sentencing disparities since the 1980s. There has been some decline in the magnitude of racial and ethnic disparities, with changes in drug laws aligning with some of the reduction in disparity at the federal level. This trend, along with the pattern of findings from related studies, poses a challenge to prominent theoretical explanations of sentencing disparities, including racial threat theory and the focal concerns perspective. Each of four influential theoretical explanations of racial and ethnic disparities in sentencing includes significant empirical or logical shortcomings. Advancing theoretical understanding of racial and ethnic disparity will require new data that follow cases from the point of arrest through to final disposition and include information about citizenship and victims.